Investigation of the Antioxidant Synergisms and Antagonisms among Caffeic, Ferulic and Rosmarinic Acids using the Briggs-Rauscher Reaction Method - Gojak-Salimović, Sabina; Ramić, Sabrina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2020)
Phenolic acids have been attracting huge attention over recent years due to their prominent antioxidant activity and potential health benefits. In this study, the antioxidant activity of caffeic, ferulic, and rosmarinic acids was evaluated using Briggs-Rauscher reaction method. In addition to single phenolic acids at different concentrations (50, 100, 200 and 250 µM), equimolar mixtures of two phenolic acids and all three phenolic acids were tested. The best ability to inhibit oscillations, i.e. the highest antioxidant activity showed rosmarinic acid at a concentration of 250 µM. Inhibition time of the Briggs-Rauscher oscillating reaction mixture was obtained experimentally for the different combinations of phenolic acids and compared with theoretical values calculated by adding up the effects of phenolic acids analyzed individually. The most of tested phenolic acids mixtures showed a difference in the antioxidant activity when compared to individual values of their constituents. The highest synergistic effect showed a mixture of caffeic acid and ferulic acid at a concentration of 250 µM while the highest antagonistic effect showed the mixture of caffeic acid, ferulic acid and rosmarinic acid at same concentration.